1999
DOI: 10.1007/s100249900083
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Atresia and Cytomegalovirus Infection: A DNA Study

Abstract: The cause of extrahepatic biliary atresia (EHBA) is undetermined in most instances, but an infectious agent is widely suspected. Cytomegalovirus (CMV) infection has been associated with intrahepatic bile duct destruction and paucity, raising the question of its role in EHBA. We identified 12 children in the past 5 years with biliary atresia and examined the bile duct biopsy. These showed acute/chronic inflammation and epithelial degeneration. CMV inclusions were not identified. We used in situ hybridization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 12 publications
5
58
1
1
Order By: Relevance
“…Lurie et al [35] , after studying four fatal cases of NIHC from CMV, described the presence of cytomegalic cells in the liver from two of them. None were detected in the present study or observed in cases of extrahepatic cholestasis (EHC) [36][37][38] . In CMV hepatitis following orthotopic liver transplantation (immunosuppressed patients), demonstration of cytomegalic inclusion bodies in hematoxylin and eosin sections is sufficient for a diagnosis of CMV hepatitis [39] .…”
Section: Discussioncontrasting
confidence: 60%
“…Lurie et al [35] , after studying four fatal cases of NIHC from CMV, described the presence of cytomegalic cells in the liver from two of them. None were detected in the present study or observed in cases of extrahepatic cholestasis (EHC) [36][37][38] . In CMV hepatitis following orthotopic liver transplantation (immunosuppressed patients), demonstration of cytomegalic inclusion bodies in hematoxylin and eosin sections is sufficient for a diagnosis of CMV hepatitis [39] .…”
Section: Discussioncontrasting
confidence: 60%
“…De Tomasso et al 9 describe a low accuracy of serological tests for detecting active CMV infection, with no correlation between the CMV-positive qPCR and histopathological changes reported by others. 1,13,16 Our study, however, reinforces a probable correlation. Some information suggests a worse outcome in CMV-affected patients.…”
supporting
confidence: 54%
“…1,9,13,16 Serology, CMV quantitative polymerase chain reaction (qPCR), immunohistochemistry and histology have been unable to confirm a possible role of CMV in BA aetiology. De Tomasso et al 9 describe a low accuracy of serological tests for detecting active CMV infection, with no correlation between the CMV-positive qPCR and histopathological changes reported by others.…”
mentioning
confidence: 99%
“…Likewise, group C rotavirus was found in patients with biliary atresia by Riepenhoff-Talty et al (11); however, another study failed to identify this virus (12). Conflicting studies have also been reported for cytomegalovirus (13,14).…”
mentioning
confidence: 97%